1998
DOI: 10.1080/02626669809492103
|View full text |Cite
|
Sign up to set email alerts
|

Snowmelt sensitivity to radiation in the urban environment

Abstract: Despite having the same snowmelt processes, snowpacks in urban environments experience a range of conditions different from those of rural areas. Melt is intensified at some sites due to greater radiative energy. Shading, however, can reduce radiation and melt at other sites. Changes to the radiation balance and snowpack processes have been investigated. A physical snowpack model was developed and tested against data from an impervious study plot in Sweden. Estimated surface runoff compared favourably with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Valeo and Ho, 2004;Lemonsu et al, 2010;Leroyer et al, 2010) and Scandinavia (e.g. Semádeni-Davies et al, 1998). These emphasize the need for the correct description of snow cover in hydrological models.…”
Section: Järvi Et Al: Development Of Suews For Cold Climate Citiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Valeo and Ho, 2004;Lemonsu et al, 2010;Leroyer et al, 2010) and Scandinavia (e.g. Semádeni-Davies et al, 1998). These emphasize the need for the correct description of snow cover in hydrological models.…”
Section: Järvi Et Al: Development Of Suews For Cold Climate Citiesmentioning
confidence: 99%
“…These studies have found a strong seasonality in the energy exchanges and a need for the correct estimation of anthropogenic heat emissions from building sources, notably heating in winter. Similarly, the few hydrological studies have shown strong seasonality in stormwater runoff and differences in the amount of the snowmelt when compared to natural environments (Bengtsson and Westerström, 1992;Semádeni-Davies and Bengtsson, 1998;Valtanen et al, 2013).…”
Section: Järvi Et Al: Development Of Suews For Cold Climate Citiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a case study of the town of Milton in southern Ontario, Farrell et al (2001) found that the annual peak flow is typically the result of spring flowrates. Semádeni-Davies and Bengtsson (1998) reported that northern Sweden experiences its most severe urban flooding during spring melt. Thorolfsson and Brandt (1996) reported that, in many urban areas in Norway, snowmelt and rain on frozen ground forms the most adverse runoff conditions, and not high-intensity rainfalls.…”
Section: Introductionmentioning
confidence: 99%